Safe and effective percutaneous ethanol injection therapy of 200 thyroid cysts - Halenka, Milan; Karásek, David; Schovánek, Jan; Fryšák, Zdeněk (Biomedical papers of the Medical Faculty of the University Palacký, Olomouc Czech Republic, 2020)
INTRODUCTION: Ultrasound-guided percutaneous ethanol injection therapy (US-PEIT) is a minimally invasive procedure that may be performed as an alternative to surgery for the treatment of recurrent symptomatic thyroid cysts for which simple aspiration failed. The present study aimed at assessing US-PEIT in a large cohort of patients, identifying factors influencing treatment outcome. METHODS: Retrospective analysis of 193 patients with 200 thyroid cysts who underwent US-PEIT in 2004-2018. RESULTS: The initial median cyst volume was 8.5 mL [5.5-16.0]; median final volume at 12 months after the completion of therapy was 0.5 mL [0.2-1.3]. A Volume Reduction Rate (VRR) of 95.0% [86.7-98.0] was achieved. For successful US-PEIT, relatively small total amount of ethanol was needed, on average corresponding to 20.0% [16.7-28.6] of the initial cyst volume. VRR positively correlated with the initial cyst volume and negatively with the presence of complex cyst. Multiple regression analysis showed the presence of complex cyst as an independent predictor of treatment efficacy. CONCLUSION: US-PEIT of thyroid cysts of all sizes was very successful with using total amounts of ethanol, corresponding to ≈20% of the initial cyst volume.
Keywords: dospělí; nemoci štítné žlázy; Cysts; Female; ultrasonografie; ethanol; Adult; výsledek terapie; mladý dospělý; injekce do léze; ženské pohlaví; Adolescent; lidé; Ultrasonography; cysty; Aged, 80 and over; Treatment Outcome; Ethanol; retrospektivní studie; Thyroid Diseases; Male; Aged; Young Adult; Injections, Intralesional; lidé středního věku; senioři nad 80 let; senioři; mužské pohlaví; Retrospective Studies; Middle Aged; mladiství; Humans